Molecular Detection of Enterotoxin Genes of Multiresistant Staphylococcus aureus Isolates from Different Sources of Food - Jassim, Sundus A.; Kandala, Nuha J. (Iraqi Journal of Science, 2021)
Foodborne diseases are a major risk for human health. Millions of people become sick as a result of eating contaminated food with microorganisms that cause diseases. S. aureus is considered as one of the most important pathogenic bacteria, having the ability to activate certain genes that encode for heat stable enterotoxins and cause Staphylococcal food poisoning. Thus, this study aimed to determine the prevalence of multi resistant Staphylococcus aureus that produce enterotoxins in different sources of food . Forty nine isolates were identified as S.aureus, according to morphological and biochemical tests. They were isolated from 387 different food samples from several randomly covered restaurants and supermarkets in different regions of Baghdad. Molecular diagnosis of S. aureus using specific primers for the 16S rRNA gene was carried out by Polymerase Chain Reaction (PCR ) technique . Susceptibility of 43 isolates of S.aureus was tested against 15 antimicrobial agents. The results revealed that all the isolates were resistant (100%) to mecillinam, highly resistant to vancomycine and meropenemin (74.4 %) and moderately resistant to Oxacillin, Erythromycin Cefotaxime, and Cefiximein (67.4, 60.4, 62.8, , 60.5 %, respectively), while they showed low resistance to Gentamicin (34.8%). In addition, all of these isolates were susceptible to Tigecycline and Amoxicillin/ clavulanic acid and Cefoxitin-Cloxacilin. High percentages of oxicillin resistant S. aureus were isolated from cooked food samples, followed by meat products, and with less percentage from pastry products. Molecular detection of enterotoxins A and B of Staphylococcus aureus isolates was performed using specific primers based on PCR. The results revealed that S. aureus isolated from cooked food had the highest percentage of the isolates producing the enterotoxins A and B. Type A enterotoxin gene showed a higher prevalence than type B gene among cooked food , dairy products and pastry. In conclusion, the results revealed a high prevalence of some classical enterotoxin genes in multi-drug resistant S.aureus isolated from different sources of food, which can cause food-poisoning and, consequently, a potential serious problem for public health.